2012
DOI: 10.1097/nmc.0b013e31824921b4
|View full text |Cite
|
Sign up to set email alerts
|

Review of Perinatal Partner-Focused Smoking Cessation Interventions

Abstract: One of the primary barriers to smoking cessation among pregnant women who smoke is having a partner who smokes. Prenatal tobacco exposure has been demonstrated to negatively affect infant health outcomes. Many smoking cessation interventions have been targeted at women who smoke in pregnancy, although research has indicated that one of the main barriers to cessation is lack of partner support. The family systems theory frames prenatal smoking cessation interventions in an inclusive manner for the woman and her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Past literature supports prenatal education on smoking (Duckworth & Chertok, 2012), and our findings support the acceptability of adding information about THS into these interventions. Although fathers may be more motivated for smoking cessation after their baby is born (Brenner & Mielck, 1993;Winickoff et al, 2010), our study lends further support to the acceptability of proactively delivering brief smoking cessation interventions to smoking fathers during their partners' routine prenatal and postpartum care.…”
Section: Nursing Implicationssupporting
confidence: 86%
See 1 more Smart Citation
“…Past literature supports prenatal education on smoking (Duckworth & Chertok, 2012), and our findings support the acceptability of adding information about THS into these interventions. Although fathers may be more motivated for smoking cessation after their baby is born (Brenner & Mielck, 1993;Winickoff et al, 2010), our study lends further support to the acceptability of proactively delivering brief smoking cessation interventions to smoking fathers during their partners' routine prenatal and postpartum care.…”
Section: Nursing Implicationssupporting
confidence: 86%
“…Presenting smokers with personalized normative feedback, such as expired carbon monoxide (CO) levels, is one particular strategy often used in combination within an MI intervention for smoking cessation that may be well suited for more resistant smokers (Butler, Rollnick, Bachmann, Russell, & Stott, 1999;Hettema & Hendricks, 2010). Although few intervention studies to date tailored to expectant or new fathers have shown limited but promising effects in increasing smoking cessation rates compared with usual care (Duckworth & Chertok, 2012;Gage et al, 2007), none was tailored to the unique smoking motives (i.e., the benefits of smoking and costs of quitting) and quitting motives (i.e., the costs of smoking and benefits of quitting) found in smoking expectant or new fathers.…”
mentioning
confidence: 98%
“…Given the high smoking rates among other household members and friends, it is critical that smoking cessation interventions target both pregnant women and those closely associated with them, especially partners. 16 Our study reiterates the need for all health professionals involved in the care of pregnant women to assess their smoking status and provide advice on smoking cessation. Cessation service provision by health professionals can be viewed negatively by some pregnant women.…”
Section: Discussionmentioning
confidence: 71%
“…The literature on interventions for partners of pregnant women, which include a broad array of designs, shows mixed results (Hemsing, Greaves, O’Leary, Chan, & Okoli, 2012). Refined approaches that access co-resident smokers’ motivation to support their partner’s and their own cessation efforts, in addition to extending the timeframe of efforts through early childhood parenting, may make greater headway (Duckworth & Chertok, 2012; Gage et al, 2007). Overall, while we found that individual characteristics are consistent correlates of maternal perinatal smoking behavior — suggesting the importance of continued public health efforts targeting individual behavior and clinical support tailored to the individual — household level and neighborhood level contextual effects merit more attention for distinct maternal age groups.…”
Section: Discussionmentioning
confidence: 99%